Occupationally Relevant Zinc‐ and Copper‐Containing Metal Fumes Inhibit Human THP‐1 Macrophage TNF and IL‐6 Responses to Bacterial Stimuli - Jan Steffens; Sabrina Michael; Katharina Kuth; Henner Hollert; Miriam Du Marchie Sarvaas; Andrijana Nesic; Thomas Kraus; Ralf Baumann (Global Challenges)
Abstract Metal workers have an increased risk of severe lobar pneumonia due to exposure to metal fume particles, which lead to recent pneumococcal vaccination recommendations. To investigate the effects of metal fume‐derived zinc oxide (ZnO) and copper oxide (CuO) particles on airway immune responses, human THP‐1‐derived macrophages are exposed in vitro to the bacterial pathogen‐associated molecular patterns (PAMPs) lipopolysaccharide (LPS), lipoteichoic Acid (LTA), or peptidoglycan (PGN), together with particle suspensions. Particles are generated through metal inert gas (MIG) soldering. Spectrometric and microscopic analysis confirms CuO and ZnO as main components. Macrophage IL‐6 and TNF mRNAs are quantified by qPCR and secreted protein levels by electrochemiluminescent multi‐spot assay. A dose‐dependent increase in macrophage TNF and IL‐6 mRNA (4 h) and protein (24 h) levels following exposure to PAMPs is significantly inhibited by 2 µg mL−1 CuO/ZnO particles (n = 5). Additionally, CuO/ZnO particles significantly inhibit TNF protein expression in unstimulated macrophages, while IL‐6 protein levels are unaffected (n = 5). The presented in vitro immunotoxicity approach may extend existing new approach methodology (NAM) elements for chemical risk assessment and possibly exposure limit evaluation refinements. These findings implicate that CuO/ZnO particles suppress macrophage proinflammatory responses to PAMPs, potentially compromising lung immunity, underlining current vaccine recommendations and efforts for preventive occupational health guidelines.